The Role of Spiritual Leaders in Building Socio-Cultural Communication Networks in the Buddhayana Community of Lampung Province - Rapiadi Rapiadi; Resdhi Wibawa; Ine Yudhawati; Widiyanto Widiyanto; sidharta adi gautama (LPPM STIAB JINARAKKHITA LAMPUNG, 2023)
This research aims to explore the role of spiritual leaders in shaping and strengthening socio-cultural communication networks in the Buddhayana community. The research focus involves analyzing the active role of spiritual leaders in facilitating interaction, maintaining cultural values, and forging interpersonal connections among Buddhists. This research method uses a case study with a qualitative approach with in-depth interviews with spiritual leaders, community members, and participatory observations at religious activities. The results showed that spiritual leaders have a crucial role in shaping and maintaining socio-cultural communication networks. Not only acts as a spiritual leader but also as a facilitator of communication between individuals in the community. Spiritual leaders also play a role in transmitting Buddhayana values, promoting collaboration, and building solidarity among community members. The study also identified factors that influence the effectiveness of the role of spiritual leaders in the context of socio-cultural communication, including active involvement in daily activities, adaptability to technological developments, and the ability to understand community needs. These findings have important implications in understanding communication dynamics in the context of Buddhayana and may contribute to practical thinking to support spiritual leaders and Buddhayana communities in strengthening their socio-cultural communication networks. This research can serve as a foundation for the development of more effective strategies to maintain the sustainability of communication and cultural values within the Buddhayana community and may be applicable to other religious and cultural contexts.